Tantangan dan Hambatan Pendidikan Anti Korupsi di Sektor Pendidikan - Cantika, Azzahra Bunga; Sari, Hermita Liana; Indiana, Putu Nanda Karenita (CV WAHANA PUBLIKASI, 2025)
Indonesia still faces major challenges in eradicating corruption that has taken root in various sectors of life. Corruption is an act of abuse of authority or position with the aim of obtaining personal or group benefits, which is carried out illegally and harms the rights of other parties. This phenomenon not only hinders national development, but also damages the moral order and public trust in state institutions. Therefore, education, especially character education, plays a crucial role in efforts to prevent corruption from an early age. Character education not only teaches moral and ethical values, but also equips the younger generation with critical thinking skills, honesty, and high social responsibility. The challenges in the digital era are increasingly complex, because children and adolescents are increasingly exposed to content and interactions that can influence their mindset and behavior. To answer these challenges, synergy is needed between educators, parents, and the community in instilling anti-corruption values ​​through an adaptive, value-based, and contextual educational approach to the development of the times. In addition, the state’s commitment to the protection and development of children as regulated in Article 28B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, is a strong legal basis for integrating anti-corruption education into the national education system. Thus, holistic and sustainable education is expected to be able to form the character of the nation’s generation that is anti-corruption in order to create a clean, just and dignified Indonesia.